-113+5x=-9x+41

Simple and best practice solution for -113+5x=-9x+41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -113+5x=-9x+41 equation:


Simplifying
-113 + 5x = -9x + 41

Reorder the terms:
-113 + 5x = 41 + -9x

Solving
-113 + 5x = 41 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-113 + 5x + 9x = 41 + -9x + 9x

Combine like terms: 5x + 9x = 14x
-113 + 14x = 41 + -9x + 9x

Combine like terms: -9x + 9x = 0
-113 + 14x = 41 + 0
-113 + 14x = 41

Add '113' to each side of the equation.
-113 + 113 + 14x = 41 + 113

Combine like terms: -113 + 113 = 0
0 + 14x = 41 + 113
14x = 41 + 113

Combine like terms: 41 + 113 = 154
14x = 154

Divide each side by '14'.
x = 11

Simplifying
x = 11

See similar equations:

| 6x-3=16-63 | | 3x-9=-13 | | 8Y-5=4A-3 | | 7(1)+3(2)= | | 9x-40=60+4x | | 12x^2+17x-13=-8 | | 12+32=12x-7 | | 4x+12=30-6x | | 3x+8y-5x-1y=0 | | 7d-2=14d-9 | | 15c^2+60=45 | | 5a+6b=50 | | 8-(-9/4) | | -25-2x=-108-8x | | 8-9/4 | | 6b+12=b+42 | | -[9z-(12z+8)]=8+(2z+10) | | 8x+2.4=7.2 | | 4x-9y-7x+5y= | | -5x+2=-4(2x+4) | | -9x-26=-80 | | 15(x+8)=180 | | x+4/8=x-2/6 | | 12-8n=14 | | -45-7x=-115 | | 7e+118=19e+10 | | -45-2x=14-10x | | 25-8x=129 | | d/2-1.3 | | 6a-9=a+46 | | 57=15-6x | | 3r+24/9=5r-30/5 |

Equations solver categories